Needs Analysis for Design Optimization Psychoeducative Guidance Service Device in Elementary School - Arismunandar, Arismunandar; Saman, Abdul; Musfirah, Musfirah; H, Nurhikmah; Burhan, Imron (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to analyze the need to optimize the design of psychoeducational guidance services in elementary schools. A descriptive quantitative approach was applied, and questionnaires were distributed to teachers and students, serving as the primary data collection tool. The analysis employed descriptive statistical techniques to illustrate elementary school students' needs for psychoeducational guidance services. The process of descriptive statistical analysis involves several steps: first, gathering data through questionnaires; next, presenting the data in a visual format such as frequency percentage tables for each indicator; and finally, interpreting the presented data. The results of the study indicate an urgent need for more comprehensive guidance and counseling services that are structured, innovative, and effective in meeting students' needs and supporting their holistic development, both in academic and personal aspects. The absence of BK teachers in elementary schools, challenges in student learning motivation, and variations in the use of learning methods and media appropriate to students' learning styles indicate the need for special interventions. Social support from family, friends, and teachers and a conducive school environment are important factors that need to be strengthened through psychoeducational guidance service devices. By focusing on developing interactive teaching materials and effective guidance strategies, this service can increase students' motivation, participation, and self-confidence, thereby supporting a more optimal learning process.